Research on stress alternation effects and fracture reorientation for refracturing treatment. (February 2021) - Lu, Mingjing; Su, Yuliang; Wen, Zhehao; Zhan, Yaohua; Almrabat, Abdulhadi
Trying to induce fracture reorientation in refracturing is important because it means stimulating areas with more residual oil and intersecting less depleted pressure. To verify the possibility of reorientation during refracturing, a hydraulic–mechanic coupling model is built and solved using COMSOL Multiphysics based on poroelastic and seepage theory; pore porosity and strain change of formation are analyzed and verified to alter the stress around the fracture; then the dynamic stress field of depleting development is obtained; factors that cause the alternation of stress are analyzed by comparing the altered minimum and maximum horizontal stress; and the area of stress reversal region is calculated. To further evaluate the oil recovery of different angles of reoriented fractures, geological and numerical models are simulated using data of an actual reservoir with a rhombus inverted nine spots well pattern. The results show that producing underground liquid leads to a change of the pore pressure and the change of direction perpendicular to the fracture is less than that parallel to the fracture, which will cause heterogeneous distribution of the stress field. It is shown that as stress change induced by the producing well parallel to the fracture alters more than that perpendicular to the fracture around the drainage area, the stress alternation can even reach the extent to which the initial minimum horizontal stress exceeds the initial maximum horizontal stress in an ellipse around the fracture. Calculation of the stress reversal region area shows that this area expands significantly in the early developing term and then slows down in natural depletion reservoirs, which indicates the possibility of fracture reorientation during refracturing. In addition, with optimal angles that exist for reoriented fractures during refracturing design and with the proper induced reoriented fractures, more oil will be recovered for field restimulation treatments. This research offers a method to determine the area of the stress reversal region and helps to select candidate wells for refracturing treatment.